2013
DOI: 10.1016/j.hrthm.2013.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of atrial late gadolinium enhancement imaging that correlates with endocardial voltage and clinical outcomes: A 2-center study

Abstract: BackgroundFor late gadolinium enhancement (LGE) cardiovascular magnetic resonance (CMR) assessment of atrial scar to guide management and targeting of ablation in atrial fibrillation (AF), an objective, reproducible method of identifying atrial scar is required.ObjectiveTo describe an automated method for operator-independent quantification of LGE that correlates with colocated endocardial voltage and clinical outcomes.MethodsLGE CMR imaging was performed at 2 centers, before and 3 months after pulmonary vein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
128
2
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(143 citation statements)
references
References 25 publications
2
128
2
11
Order By: Relevance
“…The number of points in our study was greater than in 3 previous studies comparing these 2 parameters, [1][2][3] and the weak correlation seen in all 20 patients (including 12 with over 300 points) makes insufficient point density an improbable cause for the negative result.…”
Section: Response To Letter From Bisbal Et Al Regarding "Repeat Leftcontrasting
confidence: 77%
“…The number of points in our study was greater than in 3 previous studies comparing these 2 parameters, [1][2][3] and the weak correlation seen in all 20 patients (including 12 with over 300 points) makes insufficient point density an improbable cause for the negative result.…”
Section: Response To Letter From Bisbal Et Al Regarding "Repeat Leftcontrasting
confidence: 77%
“…Although previous studies have suggested a relationship between LGE CMR signal intensity and atrial endocardial voltage, 10,15,16 this study demonstrates that there is only a weak point-by-point relationship between the 2 parameters and that low endocardial voltage can occur at sites of low and high CMR signal intensity. Furthermore, using an objective method of assessing gaps in ablation lesions, LGE CMR is unable to reliably predict the sites of electrical conduction.…”
Section: Discussioncontrasting
confidence: 76%
“…16 No statistical difference was seen above 5 SD, and the authors concluded that signal intensities above this might represent fully scarred atrial myocardium. However, this would not explain the lack of statistical significance at 0 to 3 SD.…”
Section: Correlation Between Lge Cmr and La Endocardial Voltagementioning
confidence: 97%
“…20 In clinical studies, despite improvements in MRI quantification of fibrosis, spatial and temporal correlation with known electrophysiological measures are weak. Despite work correlating the extent of late gadolinium enhancement MRI with AF recurrence 21 and our recent point-by-point correlation of enhancement and voltage (Figure 3), 22 identifying the late gadolinium enhancement MRI signature of areas critical to AF stability remains elusive. It is striking that concurrent MRI or any other structural data from any of the groups advocating the hierarchical model demonstrating rotors in persistent human AF has not been presented but must be addressed if this paradigm is to be strengthened.…”
Section: Fibrosismentioning
confidence: 97%